A DESCRIPTIVE STUDY ON THE STUDENTS’ COMPETENCE IN TRANSLATING ENGLISH COMPOUND – COMPLEX SENTENCE INTO INDONESIAN (A CASE STUDY OF THE FIFTH SEMESTER STUDENTS OF ABA ST. PIGNATELLY IN SURAKARTA) - SETIYANI , ATIEK (2007)
The purposes of this research are to know the students’ competence in translating English compound complex sentence into Indonesian done by the students of ABA St. Pignatelly and to find the difficulties faced by the fifth semester students of ABA St. Pignatelly in translating English compound- complex sentence. The type of this research is descriptive qualitative research. The data of this study are the result of student’s translation and the data source is test given to the students containing 25 English compound-complex sentences. In this research the writer takes the fifth semester students of ABA St. Pignatelly in Surakarta as respondent. The methods of collecting data used in this study are document and interview in this study. The result of the research show that firstly, the students competence in translating is fair. The writer finds that from 750 data, there are 379 or 50,53% is correct answer and 371 or 49,47% is incorrect answer. Secondly, the writer finds the problems faced by students in translating English compound-complex sentence are limited vocabulary, word-for-word oriented, students seldom use compound-complex sentence and the students did not adjust the meaning of word with context.